Komunikasi Politik Bilhikmah Datuk Kalampayan Dan Relevansinya Dewasa Ini (Universitas Bina Sarana Informatika, 2022)
The Political Communication Research of Sheikh Muhammad Arsyad al-Banjari in the Sultanate of Banjar originated from his work that contributed to the sultan of Banjar at that time. among them; the formation of the crown counsel, the writing of the Kitab of Sabil al-Muhtaddin at the request of the Sultan of Banjar made a book on the fight of Malay-language worship, the judicial institution (the institution of karakatan qadhi), the manufacture of irrigation. This research aims to find out and analyze the approach of political communication Datuk Kalampayanin the sultanate of Banjar, the political communication model Datuk Kalampayan, and the application of the Datuk Kalampayan political communication model to political parties in South Borneo. Researchers use qualitative methods with a case study approach. Data sources from primary data and secondary data were 14 (fourteen) informants. The results of this research obtained findings; First, the political communication carried out by Sheikh Muhammad Arsyad al-Banjari known as Datuk Kalampayanin the 18th century turned out to strengthen the theory of Symbolic Intractional Communication Mean in the 19th century, Secondly, Datuk Kalampayan's political communication model was followed by Banjar contributing to the discipline of communication; Third, the application of the value of Datuk Kalampayan's communication model value to political parties in South Borneo became crucial including Strengthening the firmness of faith as the foundation of life in society, nation and state. Upgrading oneself with knowledge and charity, by consistently coexisting in harmony. Not doing a frontal critique of the government, and praying for good to the government towards the benefits of mashallah.